ANALYSIS OF DAILY CAPITAL MANAGEMENT OF CULINARY MSMES IN RESPONDING TO THE QRIS SETTLEMENT MECHANISM - Mangasi Sinurat (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to analyze culinary MSMEs' understanding of the QRIS settlement mechanism, identify obstacles arising from the delay in disbursement, and explain their daily capital management practices in response to these conditions. This study used a descriptive qualitative approach with a case study design through in-depth interviews with one culinary MSME. The results indicate that MSMEs have a general understanding of the QRIS settlement mechanism, but face limited liquidity because funds from non-cash transactions cannot be used on the same day. This condition encourages business actors to adjust their daily capital management by utilizing personal savings and funds from existing cash transactions to maintain business continuity. These findings indicate that the QRIS settlement mechanism has direct implications for the daily financial management of culinary MSMEs.